Changes in daily rainfall and temperature extremes of upper Awash Basin, Ethiopia - Haftu Brhane Gebremichael; Gelana Amente Raba; Kassahun Ture Beketie; Gudina Legese Feyisa; Teshome Siyoum (Scientific African, 2022)
Climate change has an impact on rainfall and temperature. In this study, changes in rainfall and temperature extremes in Upper Awash Basin (Ethiopia) from 1983 to 2016 were investigated using daily combination of observed and satellite data of ten meteorological stations. To determine the annual trends, two non-parametric methods, namely Mann-Kendall and Sen's slope estimator were utilized. In this study, RClimDex1.1 was utilized to compute the selected temperature and rainfall extreme indices. The Inverse Distance Weighting (IDW) technique was used for spatial interpolation. The findings indicate significant trends in both annual and Kiremt (June – September) season rainfalls in two out of the ten stations, namely, Addis Alem and Koka Dam (p < 0.05). None of the ten stations exhibited significant trends for Belg (February-May) season. Overall, the mean rainfall trends of the basin indicate a considerable decline. However, from the spatial analysis, increasing rainfall and extreme events in the eastern portion of the basin were observed. Moreover, from average anomalies of the rainfall extreme indices of the entire basin showed a tendency of wetness. The maximum and the minimum temperatures displayed increasing trends in most of the weather stations (except in Addis Alem, and Kimoye for maximum temperature and Koka Dam, Hombole, Mojo, and Sendafa (AD) for minimum temperature). The temperature extreme indices showed increasing trends in TXx, TNx, TN90p, TX90p, SU25, and WSDI. The trend of the SU25 index indicated an increasing trend at 90% of the stations (p < 0.05). Overall, average anomalies of all temperature extreme indices of the entire basin (except TXn) revealed warming trends. The possible causes of these extreme events are the results of both local and global processes. Urban expansion and associated land use/cover changes could synergistically contribute to global warming. These findings are useful for the stakeholders in the region.